Shaping resilience: The critical role of plant response regulators in salinity stress - Joshi, Priyanka S.; Singla Pareek, Sneh L.; Pareek, Ashwani (Biochimica et biophysica acta. General subjects, 2025)
Salinity stress affects plant growth, development, biomass, yield, as well as their survival. A series of signaling cascade is activated to cope the deleterious effect of salinity stress. Cytokinins are known for their regulatory roles from cell growth and expansion to abiotic stress signaling. Two component system (TCS) are important multistep phosphorelay signal transduction machinery converging cytokinin, ethylene and light signal transduction pathways together. Plant TCS comprises of histidine kinases, phosho-transfer proteins and response regulators. Histidine kinases perceive the signal and relay it to response regulator via histidine containing phosphor-transfer proteins. Response regulators are one of the major and diverse component of TCS system which have been extensively studied for their role in plant growth, development and circadian rhythm. However, knowledge of their regulatory role in abiotic stress signaling is limited. This mini-review specifically focus on role of response regulators in salinity stress signaling. Response regulators is the divergent node of TCS machinery, where cross-talks with other stress-mediated, phytohormone-mediated, as well as, light-mediated signaling pathways ensues. Studies from past few years have established central role of response regulators in salinity stress, however, the detailed mechanism of their actions need to be studied further. Response regulators act as both negative as well as positive regulator of salinity and cytokinin signaling, making it an excellent target to increase crop yield as well as stress tolerance capabilities. •Cytokinin plays a key role in plant growth, development and abiotic stress signaling.•Response regulators are one of the three component of Two Component System involved in cytokinin signaling.•Response regulators are comprehensively studied for their role in plant growth, development and circadian rhythm.•However, studies focusing on their role in abiotic stress signaling have been gaining momentum in the past decade.•This review mainly focuses on their role in salinity stress signaling.